UMTS Radio Network Evaluation and Optimization beyond Snapshots - Eisenblätter, Andreas; Geerdes, Hans-Florian; Koch, Thorsten; Martin, Alexander; Wessäly, Roland (Mathematical Methods of Operations Research, 2006)
A new evaluation scheme for universal mobile telecommunications system (UMTS) radio networks is introduced. The approach takes the complex coupling of coverage and capacity through interference into account. Cell load estimates, otherwise obtained through Monte-Carlo simulation, can now be approximated without time-consuming iterative simulations on user snapshots. The two cornerstones are the generalization of interference coupling matrices from user snapshots to average load and the emulation of load control by an analytical scaling scheme. Building on the new evaluation scheme, two novel radio network optimization algorithms are presented: an efficient local search procedure and a mixed integer program that aims at designing the coupling matrix. Computational experiments for optimizing antenna tilts show that our new approaches outperform traditional snapshot models.
Keywords: Network design; Network planning; UMTS radio interface